Estrutura hierárquica na resposta das distribuições geográficas de plantas do Cerrado à mudanças climáticas - SOUSA, Nayara Pereira Rezende de (2011)
The climate can be considered an extremely important factor in vegetation distribution and its characteristics in a global context. Climate changes affect the global distribution of vegetation in the distant past and probably will affect in the future. Spatial distribution models of species (SDMs), also known as niche models are one of the best current tools for predicting climate-induced changes on the distribution of species. In general, studies of the consequences of climate changes on the distribution of biomes include only the geographic distribution of the biome or the species are analyzed individually. The availability of climatic and ecological data on a large scale, in addition to more efficient procedures for obtaining data from geographic information systems, optimization programs and greater computing power favor the process of modeling the potential distribution, and broaden the effectiveness of results available by the SDMS. The main objective of this study is to evaluate whether there is a shift in the hierarchical structure of future distributions of biome, phytoeeological regions and plants species of the biome under the effect of climate changes. Consequently, we evaluate some effects of climate changes on the pattern of species richness and pattern of future distributions of the biome, phytoeeological regions and species. This study shows that there is a hierarchical structure in the response of vegetation distribution faces climate changes predictions for the year 2080 in the Brazilian Cerrado. In general, in the three scales studied their distributions are moving toward to southeast of Brazil, thus this region is replaced by a diversity gain while the rest of the local Cerrado suffers from the impoverishment of their diversity. This study also shows that in the near future, the Cerrado species will show habitat loss, due to both the loss of fragments and area reduction of these.